Perancangan Alat Micro Hydroelectric Portable dengan Menggunakan Sistem Turbin Archimedes Screw - Putra, Wikra Wardhana Wijaya; Risnawati, Risnawati; Rohminatin, Rohminatin (Forum Kerjasama Pendidikan Tinggi, 2022)
Micro Hydroelectric portable is a small-scale hydroelectric power plant (< 100 kW) which has many advantages, especially without the use of reservoirs, is environmentally friendly, and is a renewable energy, so many are built for power generation purposes in rural areas. Micro Hydro is generally a permanent generator, so the main problem faced is the relatively expensive construction cost. The prototype of a Portable Micro Hydro Power Plant using an Archimedes screw turbine is a power plant that is capable of working on small-scale water discharge in the form of a beam with a length of 80 cm, a width of 40 cm, a turbine housing slope of 45o and a total weight of 8 Kg, making it a portable Micro Hydro. Micro Hydro works at a water flow rate of 0.1 - 1.1 m3/second using an Archimedes screw turbine which can work at low heads. Power from the Archimedes screw turbine is channeled to the generator using a 1:3 ratio, where one rotation of the turbine produces three rotations of the generator producing an average voltage of 7.3 Volts DC, then the voltage is converted by the inverter, charger controller, battery for 12 Volt loads, 12 Watt generated power capacity